2021
DOI: 10.3390/su13063401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cradle-to-Grave Life Cycle Assessment of Low and Mid-Rise Mass Timber Buildings with Equivalent Structural Steel Alternatives

Abstract: The objective of this paper was to quantify and compare the environmental impacts associated with alternative designs of typical North American low and mid-rise buildings. Two scenarios were considered: a traditional structural steel frame or an all-wood mass timber design, utilizing engineered wood products for both gravity and lateral load resistance. The boundary of the quantitative analysis was cradle-to-grave with considerations taken to discuss end-of-life and material reuse scenarios. The TRACI methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 26 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…In comparing the carbon emissions obtained from both buildings, during the production stages of the building materials, it was found that House A emitted around 50.43% fewer carbon when compared to the carbon emissions of House B. Cole and Kernan [65] found that timber frames' extraction and manufacturing processes have fewer energy usage when compared to other building materials such as concrete and steel. A comparative study between a mid-rise mass timber building and a steel building also indicated that the timber building produced between 28.99% and 34.08% of fewer embodied carbon (A1-A5) than the steel building [66], which confirms that the results obtained in this study are in line with the literature findings. In addition, carbon emissions from the two buildings during their remaining life stages were shown to be similar.…”
Section: Comparison Of the Results Obtained From The Two Housessupporting
confidence: 91%
“…In comparing the carbon emissions obtained from both buildings, during the production stages of the building materials, it was found that House A emitted around 50.43% fewer carbon when compared to the carbon emissions of House B. Cole and Kernan [65] found that timber frames' extraction and manufacturing processes have fewer energy usage when compared to other building materials such as concrete and steel. A comparative study between a mid-rise mass timber building and a steel building also indicated that the timber building produced between 28.99% and 34.08% of fewer embodied carbon (A1-A5) than the steel building [66], which confirms that the results obtained in this study are in line with the literature findings. In addition, carbon emissions from the two buildings during their remaining life stages were shown to be similar.…”
Section: Comparison Of the Results Obtained From The Two Housessupporting
confidence: 91%
“…For example, Švajlenka et al [19] reported the commercial availability of process databases for material and energy flows to improve on the lack of data for LCA. An analysis of state of the art in the integration of LCA with building information modeling (BIM) for data management [20][21][22] highlights many benefits: the integration of BIM-LCA with environmental product declarations (EPDs) for detailed and accurate data for a life cycle inventory [23]; the integration of building LCA and BIM's standard industry foundation classes (IFC) to reduce access barriers and assessment effort/time [24,25]; the comparison of LCAs of buildings with different material structure alternatives [26]. These advantages are the point of departure for assessing the relevance of an exergy-based LCA of buildings.…”
Section: Literature Review: Relevance Of Exergy To a Building Life Cycle Assessmentmentioning
confidence: 99%
“…Though the EPDs and building rating systems provide high-level environmental impacts scores of buildings materials and whole buildings, to better understand the detailed process level embodied energy and emissions, these impacts need to be analyzed from a life cycle perspective. Over the last few decades, LCA studies have been carried out to evaluate building materials (Rivela et al 2006;Ingrao et al 2016;Bergman and Bowe 2008;Bahramian and Yetilmezsoy 2020;Allan and Phillips 2021;Dascalaki et al 2021;Salazar and Sowlati 2008) and sustainability performance of buildings (Kylili, Ilic, and Fokaides 2017;Zuo et al 2017;Hasik et al 2019;Al-Ghamdi and Bilec 2017).…”
Section: Introduction 11 Building Life-cycle Analysis To Address Embodied Carbon and Energy Usementioning
confidence: 99%